PENGEMBANGAN MODUL PRAKTIKUM UNTUK PERBANDINGAN UNJUK KERJA SUMBER CAHAYA OPTIK LED DAN LASER DALAM SISTEM KOMUNIKASI OPTIK - Ni Komang Utari Yulianingsih; Pande Ketut Sudiarta; Nyoman Putra Sastra (Program Studi Teknik Elektro UNUD, 2021)
LED optical light source and laser diode function as an information carriers in the opticalcommunication systems. Each optical light source in the form of LED, CW Laser, and VCSEL Laserhas advantages and disadvantages. Based on these advantages and disadvantages, a study wascarried out on the internal and external characteristics of optical light sources to determine the optimaloptical light source to use as needed. Simulations are carried out in optical system software. Theperformance analyzed is Q-Factor, BER, and Eye Diagram until it reaches the ITU-T G.984.2standard with a minimum limit of Q-Factor = 6 and BER = 10-9. The feasibility test of the practicummodule uses the method of filling out a questionnaire with a Likert scale of 1–5 and giving pre andpost-test to the practitioner. The results of this study were an increase in the internal characteristics ofthe LED, a decrease in the signal power of the CW Laser, and an increase in the bias current of theVCSEL Laser resulting in a decrease in Q-Factor, and an increase in the BER value. The comparisonof the increase in bit rate and transmission distance showed that CW Laser can transmit a higher bitrate and a longer transmission distance. The comparison of the transmission distance that can becovered by each optical light source shows that the CW Laser travels the farthest transmissiondistance . Increased understanding of the practitioner based on the post-test score which is higherthan the pre-test score can be used as the basis that this practicum module as a whole is verysuitable for use as teaching material. This is also supported by the feasibility test of the questionnairefilling method with a Likert scale of 1-5 with a percentage of the practitioner's assessment of 88.6%.